2013
DOI: 10.1007/s11999-013-3185-2
|View full text |Cite
|
Sign up to set email alerts
|

Coronal Limb Alignment and Indications for High Tibial Osteotomy in Patients Undergoing Revision ACL Reconstruction

Abstract: Background Failed ACL reconstruction frequently is accompanied by irreparable medial meniscal tear and/or visible osteoarthritis (OA) in the medial tibiofemoral joint. Thus, assessment for the presence of varus malalignment is important in caring for patients in whom revision ACL reconstruction is considered. Questions/purposesWe determined whether patients undergoing revision ACL reconstruction (1) have more frequent varus malalignment coupled with more severe degrees of medial meniscal injury and/or medial t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 23 publications
1
28
0
Order By: Relevance
“…However, the current study did not evaluate the effect of realignment surgery, and more research is necessary to assess this possible relationship. Our findings are consistent with a recent study reporting that many rACLR patients are good candidates for high tibial osteotomy 45 .…”
Section: Discussionsupporting
confidence: 93%
“…However, the current study did not evaluate the effect of realignment surgery, and more research is necessary to assess this possible relationship. Our findings are consistent with a recent study reporting that many rACLR patients are good candidates for high tibial osteotomy 45 .…”
Section: Discussionsupporting
confidence: 93%
“…This higher incidence is also confirmed by several studies that compared the radiographic preoperative and postoperative results of revision ACL with a matched group of primary reconstruction,3 19 26 which showed an increased percentage of patients with varus malalignment and medial OA already at preoperative status, and an almost double-fold incidence of OA changes after 2.8–8 years. Moreover, the same studies reported a higher incidence of meniscal and chondral lesions in patients who sustain revision ACL reconstruction.…”
Section: Discussionmentioning
confidence: 55%
“…However, it could be assumed that the reported results could be non-specifically generalised for any kind of revision reconstruction, because no exclusion criteria based on surgical technique or patient's characteristics were applied. Also, the lack of OA evaluation with long leg radiographs could represent a bias for this study, as the importance of lower limb alignment in the primary and also revision ACL reconstruction has been extensively underlined 4 26 30–32. Lastly, the choice to consider 4 years as the minimum follow-up required for study inclusion reflects the paucity of the available literature, and could be considered a compromise between the necessity to obtain a sufficient number of studies and the minimum period to detect noticeable OA signs or OA progression.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10] Among these, recurrent symptomatic instability typically requires a revision ACL reconstruction and is frequently combined with other complications such as meniscal tears, limitation of motion, or OA. 11 These combined | 2605 CHANG et Al.…”
Section: Introductionmentioning
confidence: 99%
“…However, a subset of patients needs additional surgery because of complications such as recurrent symptomatic instability, meniscal tears, osteoarthritis (OA), or stiffness . Among these, recurrent symptomatic instability typically requires a revision ACL reconstruction and is frequently combined with other complications such as meniscal tears, limitation of motion, or OA . These combined pathological conditions can affect the overall clinical results after revision ACL reconstruction.…”
Section: Introductionmentioning
confidence: 99%